Airway obstruction during pneumonectomy using a single lumen tube: A case report. Issue 16 (April 2020) - Son, Shill Lee; Kim, Woo-Shik; Kwon, Miyoung; Moon, Yeon-Jin
Abstract: Rationale: Endotracheal intubation is an essential step for airway management during general anesthesia. When surgeons carry out thoracic surgery such as pneumonectomy, they usually request lung isolation to secure a clear surgical view. A double lumen endotracheal tube is used for lung isolation in routine thoracic surgeries. Patient Concerns: A 56-year-old man was previously diagnosed with left Aspergilloma, a tuberculosis destroyed lung, and diabetes mellitus. According to his chest x-ray and chest computed tomography, his left lung was nearly collapsed, and the result of a pulmonary function test was severely restricted. The patient's diffusing capacity for carbon monoxide was 63% and predicted postoperative forced expiratory volume in 1 second was 23.5% Diagnoses: Due to his previous history, radiologic findings and laboratory test results, he was diagnosed with left Aspergilloma and tuberculosis destroyed lung. Interventions: Due to recurrence of Aspergilloma in his left lung, the patient was scheduled for a left pneumonectomy. Since the patient's partial oxygen concentration was adequate despite his left lung being nearly totally collapsed, we thought that we would be capable of performing the pneumonectomy using a single lumen tube (SLT). For a better surgical view, we planned lung isolation via insertion of a SLT deep into the bronchus. Outcomes: During pneumonectomy, after tracheal suction was performed, we tried a lung recruitment maneuver. Suddenly end-tidal carbon dioxide did not show on the monitor. The patient's blood pressure dropped and heart rate was decreasing. We thought that cardiopulmonary resuscitation was needed and an approximately 2 cm sized hematoma was removed from the endotracheal tube after vigorous suctioning. After getting rid of the hematoma, we changed the single tube to a double lumen tube (DLT). Lessons: This case led us to the conclusion that a DLT should be used for safety when carrying out thoracic surgery. We report a rare case of an airway obstruction using a SLT during pneumonectomy.